Comparison of the Effect of Face-to-Face and Distance Learning on Knowledge, Attitude and Practice of Females about Breastfeeding in Shiraz, Iran: A Randomized Controlled Trial - Leila Ghavami; Tayebeh Rakhshani; Zahra Motlagh; Aboubakr Jafarnejad; Azizallah Dehghan (Shiraz University of Medical Sciences, 2023)
Background: The present study aimed to compare the effect face-to -face and distance learning on knowledge, attitude and practice of females about breastfeeding in Shiraz, Iran.Methods: This randomized controlled trial was conducted in Shiraz, Iran in 2019 on 313 women who were referred to health centers (93 face-to face group, 105 distance learning group, and 115 control group). The study outcomes included knowledge, attitude, and practice of the women about breastfeeding which were measured at the onset and one-month post-intervention. The data were analyzed using SPSS 21 software.Results: Mean changes of knowledge and attitude were significantly higher in the face-to-face and distance learning intervention groups compared to the control group (P<0.05). Mean practice changes from the baseline until one month after the intervention was significantly higher in the face to-face intervention group compared to the control group (P=0.015) and in the face-to-face intervention group compared to the distance learning intervention group (P=0.002).Conclusion: The present study showed that both face-to-face and distance learning breastfeeding interventions effectively increased the mothers' knowledge and attitudes, and that faceto- face intervention would led to improved practice.